Osteosarcopenia in women with rheumatoid arthritis: association with nutritional status and physical condition - O. V. Dobrovolskaya; A. Yu. Feklistov; N. V. Demin; M. V. Kozyreva; N. V. Toroptsova (Современная ревматология)
Objective: to evaluate nutritional status, muscle strength, functional status of skeletal muscles and physical activity (PHA) and their relationship with the osteopenic body composition phenotype in women in post menopause with rheumatoid arthritis (RA).   Material and methods. The case-control study included 134 women in post menopause with RA, 52 of them had osteosarcopenia (OSP) according to densitometry and 82 had no decrease in bone mineral density (BMD) and muscle mass (mean age 62.0 ± 7.2 and 59.6 ± 7.5 years, respectively; p > 0.05). A clinical and laboratory examination as well as tests to assess muscle strength and functional status were performed. The MNA-SF and IPAQ questionnaires were used to determine nutritional status and physical activity.   Results and discussion. Malnutrition was found in 51.9 % of patients, and low and average levels of PHA were found in 5.8 and 50.0 % of patients with OSP, respectively. Factors associated with OSP were identified: nutritional status according to MNA-SF < 12 points (odds ratio, OR 2.52; 95 % confidence interval, CI 1.10–5.77; p = 0.029), dietary calcium intake < 500 mg/day (OR 3.23; 95 % CI 1.49–7.01; p = 0.003), 25(OH)D level < 30 ng/ml (OR 4.55; 95 % CI 1.86–11.16; p = 0.001), moderate PHA < 1 hour per day (OR 2.67; 95 % CI 1.06–6.75; p = 0.037), walking < 1 hour per day and < 4 hours per week (OR 3.25; 95 % CI 1.26–8.38; p = 0.015 and OR 3.17; 95 % CI 1.19–8.46; p = 0.021, respectively).   Conclusion. Reduced nutritional status was found in 51.9 % and average or low levels of PHA in 55.8 % of patients with OSP. The risk of OSP development was increased by low nutritional status, inadequate dietary calcium intake, low vitamin D levels, short duration of daily moderate exercise, and inadequate daily and weekly walking time.